Perubahan Iklim dan Dampaknya Terhadap Masyarakat di Daerah Mampang dan Bojongsari - Isnaini Putri Az-Zahra; Bhita Cahya Kiara; Muhammad Fattan Fachrezy; Aidil Firman Majid; Arif Saefudin (Geosfera: Jurnal Penelitian Geografi, 2025)
Climate change is a serious issue that has been widely discussed recently, including the phenomenon of wet droughts. In the two areas studied, Mampang and Bojongsari in Depok, West Java, significant weather changes often occur. This study aims to determine the impact and ways to mitigate it in the communities of both areas. The method used was descriptive qualitative with data collection through interviews with a number of local residents of Mampang and Bojongsari. The results show that the impact that still frequently occurs in both areas is flooding. Sources in both areas also mentioned that recently, the weather has undergone noticeable changes. Some residents in both areas need appropriate and in-depth education to minimise casualties. In conclusion, this discussion on climate change narrowed down to the concerns of local residents in the Mampang and Bojongsari areas regarding the health impacts and major disasters such as floods and strong winds. The health impacts include the easy emergence of diseases such as dengue fever or flu, which can strike at any time. Therefore, education on disaster mitigation and disease prevention needs to be provided to residents so that they become more open to the current impacts of climate change.